Pelatihan Rancangan Evaluasi Pembelajaran Ipa Kelas Tinggi Berbasis Hots Bagi Guru Sekolah Dasar - Dinda Widyastika; Nur Wahyuni; Fathyah Nabila; Salsabilla (Outline Journal of Community Development, 2023)
This community service aims to assist elementary school class teachers on how to compile and develop questions based on higher order thinking (HOT). Assistance activities are carried out at SD Negeri 060970 Medan Belawan. The number of participants involved were 15 elementary school teachers from various classes. In this service activity, several methods are used, including: training and mentoring. The training was carried out using lecture, discussion, and question and answer techniques regarding the preparation of HOTS-based questions. While mentoring is carried out to provide skills in developing HOTS-based questions and changing ordinary questions into HOTS questions. The result of this training activity is to increase teachers' understanding in developing HOTS-based questions in high grades. This can be seen from the product of the HOTS-based questions that have been compiled by the teacher.